EVALUASI SISTIM SURVEILANS EPIDEMIOLOGI DEMAM BERDARAH DENGUE DI DINAS KESEHATAN KABUPATEN JEMBER - Wahjudi, Pudjo; Juwita, Asri (FKM - UNEJ, 2007)
In District of Jember almost every year appears Dengue Haemorrhagic Fever (DHF) cases, its peak happened in 2005 with 1079 cases. DHF is one of the contagious disease that need to be prevented and fought against because its could cause death and potentially be extraordinary event. To overcome this problem an effective and efficient surveillance system is needed to monitor the existence of this disease as early as possible to make prevention from its widespread. The goal of this research is to evaluate DHF epidemiologic surveillance in the Health Department of Jember District by identifying the way of conducting surveillance system, evaluating the surveillance system based on the surveillanceâs attribute as well as identifying the weakness of the surveillance system. This research applies descriptive analysis method that is describing a certain situation objectively. The respondents are staffs who were responsible to handle DHF data referring to 49 Center of Public Health Service, 8 Hospitals and also 1 staff ofÂ Jember District Health Department. The result of this research indicates that in conducting DHF surveillance system the completeness of data report is still unfit with its indicator, the flow of the reports is in line with the correct procedure, there were data compilation, analysis and data interpretation and also information desemination meanwhile there were not optimal feedback. The evaluation based on surveillance attribute indicates that DHF epidemic surveillance system is simple, representative, acceptable and flexible with Positive Predictive Value and sensitivity more tha 80%, meanwhile there were no accurate data report even thought oral report always came on time. There must be a control system in collecting data. Beside that there must be good training for the surveillance staff, for surveyor in Hospitals or Center of Public Health Service and more qualified feed back must be provided by report takers.Â Keywords : DHF, surveillance system, evaluation